Association between shift work and extended working hours with burnout and presenteeism among health care workers from Family Medicine Centres - Nurka Pranjić; Nehra Mosorović; Sabina Bećirović; Selvedina Sarajlić-Spahić (Medicinski glasnik, 2023)
Aim: To investigate the influence of irregular shifts on increased emotional, physical, and cognitive exhaustion and decreased working performance expressed by the phenomenon of presenteeism. Methods: The study sample of 405 healthcare workers from Family medicine centres completed questionnaires in two measurement time points, in 2014 (TP1) and repeated in 2019 (TP2), when 301 respondents remained in the study. Healthcare workers completed questionnaires assessing demographics, work schedules, job burnout, and presenteeism. Results: Repeated long-term exposure to rotating day-evening shifts was a significant risk for increased presenteeism (OR=1.689, 95%CI 1.042-2.739; p=0.001) and burnout (OR=1.705, 95%CI 1.237-2.352; p=0.001). Extended working hours are a predictor of presenteeism (OR=1.989, 95%CI 1.042-2.739; p=0.008). Conclusion: The adverse effects of rotating day-evening shifts on burnout and presenteeism among healthcare workers in a family medicine centre was little researched, particularly the issue of managing the risks of exposure to rotating day-evening shifts and extended working hours. This study reflects a situation of uncertainty, in which the logic of precaution is imposed on mental health, and keeps working engagements in health care workers. Appropriate management of shift work and better organization of work schedules in the primary healthcare sector protects the wellbeing of healthcare workers and patients, efficient work, and quality of health care, and invites for future research on better working schedules and introducing preventive interventions with available flexibility of working times.
Keywords: emotional; physical and cognitive exhaustion; irregular working shift; primary healthcare workers